Originally Posted by

**Wilmer** To start, more brackets required, and squareroot is same as ^(1/2); so:

a^3 b^(1/2) c^(-1/2) (ab)^(1/3)

--------------------------------- the "divided by" line

(a^3)^(1/2) (bc)^(1/2)

On your 2 "trying to figure out":

(ab)^(1/3) = a^(1/3) b^(1/3)

sqrt(a^3) = (a^3)^(1/2) = a^(3/2)

Looks like you know what you're doing!

Next step is separate (ab) and (bc):

a^3 b^(1/2) c^(-1/2) a^(1/3) b^(1/3)

-------------------------------------- the "divided by" line

a^(3/2) b^(1/2) c^(1/2)

Now, using rules:

a^x a^y = a(x+y)

a^x / a^y = a^(x-y) or 1/a^(y-z)

you should be able to wrap that up in this neat little xmas package:

a^(11/6) b^(1/3) / c